Subject-specific computational modeling of human phonation - Xue, Qian; Zheng, Xudong; Mittal, Rajat; Bielamowicz, Steven (The Journal of the Acoustical Society of America, 2014)
A direct numerical simulation of flow-structure interaction is carried out in a subject-specific larynx model to study human phonation under physiological conditions. The simulation results compare well to the established human data. The resulting glottal flow and waveform are found to be within the normal physiological ranges. The effects of realistic geometry on the vocal fold dynamics and the glottal flow are extensively examined. It is found that the asymmetric anterior-posterior laryngeal configuration produces strong anterior-posterior asymmetries in both vocal fold vibration and glottal flow which has not been captured in the simplified models. It needs to be pointed out that the observations from the current numerical simulation are only valid for the flow conditions investigated. The limitations of the study are also discussed.